Produtividade e qualidade de alho nobre sob temperatura negativa de vernalização - Azevedo, Breno Nunes Rodrigues de (2019)
Garlic crop in Brazil has been growing in recent years, mainly due to the planting of noble garlic using the most appropriate biotechnologies and management. One of the recent technologies is artificial vernalization that is the use of low temperature during the maintaining of garlic seed to break the dormancy. This technique has been allowed the garlic cultivation on no favorable areas in Brazil, and guaranteed major crop production. However, there is a low of information about the negative temperature of vernalization, that believe it cause better plant development and garlic productivity. In view of the above, the objective was to evaluate the vernalization with different temperatures (positive and negative) and visual index of dormancy (IVDs) in different planting times, using Ito seed garlic in the conditions of Cristalina Coundy, Goias State of Brazil. The experimental design was a randomized block design with four replications in a 2 x 3 factorial scheme, two IVDs 40% and 60%, three vernalization temperatures (-1ºC to -3ºC; 1ºC to 3ºC and 2ºC to 4ºC) and three planting seasons. SPAD index, plant height, total leaf number, bulb ratio, and yield of commercial bulbs were evaluated. The results showed that the use of negative temperatures in the vernalization technique provided better plant development, plant height, bulb ratio, number of leaves than other treatments. Yield increased with the combination of negative vernalization temperatures, associated with 60% IVD, it was obtained garlic of better market values. We concluded that there is a big potential for use of negative temperature vernalization of cultivar Ito, and, other studies should confirm this statement using other varieties with economic importance at Brazil.